Front Cover: A 3D Polymeric Platform for Photonic Quantum Technologies (Adv. Quantum Technol. 7/2020). Issue 7 (6th July 2020) - Colautti, Maja; Lombardi, Pietro; Trapuzzano, Marco; Piccioli, Francesco S.; Pazzagli, Sofia; Tiribilli, Bruno; Nocentini, Sara; Cataliotti, Francesco S.; Wiersma, Diederik S.; Toninelli, Costanza
Abstract : A major challenge in quantum technologies is the on‐chip integration of quantum emitters in a way that can be scaled up and preserves the emitter coherence properties. In the unconventional platform presented by Costanza Toninelli and co‐workers in article number 2000004, molecular single‐photon sources are embedded in three‐dimensional polymeric structures, obtained by direct laser writing. Anthracene nanocrystals doped with dibenzoterrylene chromophores (chemical structure in the zoom) are previously selected and integrated in a scalable way, without perturbing the emitter optical features. In particular, suspended waveguides are designed to route the emitted fluorescence towards convenient output modes while micro‐dome solid immersion lenses efficiently redirect the emission enabling unprecedented collected single‐photon rates from a cold molecule.